Familia disfuncional y su repercusión en el rendimiento académico de un niño de 7 años en el cantón Cayambe - Lema Chasi, Lady Edith (2021)
This case study presented a problem such as the dysfunctional family and its impact on academic performance, in which it was possible to gather valid and reliable information and data for the elaboration of this case, through the use of methods such as interviews and instruments. Such as psychometric evaluations such as Projective Graphic Test (HTP) and Wechsler's Intellectual Test (WISC-V) which was applied to a seven-year-old boy from the Cayambe canton, obtaining results such as: tantrums, aggressiveness, impulsivity, together with an IQ of 78 which indicates a low average level. A diagnosis of 317 (F70) Mild Intellectual Development Disorder and (313.81) F91.3 Oppositional Defiant Disorder was obtained. It was proposed as goals to improve the bonds within the family system, and in such a way the patient is integrated into their academic activities and development and interaction in classes.